The effect of representative account on tax intensification activities - Sri Rahayu; Faty Rahmarisa (Proceedings of AICS - Social Sciences, 2017)
Intensification of taxation is a way of increasing the income of the State by focusing on the activities of optimizing the extraction of income or income tax on objects and tax subjects that have been recorded in the administration of the Director General of Taxes. In conducting tax intensification then required Representative Account is a qualified human resources who can carry out their duties to provide excellent service, guidance and supervision to taxpayers in an effective and efficient way. The role of Representative Account is expected to be a liaison between the tax office and the taxpayer so that the intensification of tax activities in the done with the maximum. The purpose of this study was to determine how to influence of account representative of taxation intensification activity. This research was conducted by making a questionnaire in the form of questionnaires and interviews to employees in the KPP Pratama Medan Polonia to answer the formulation of the issues raised. Analytical technique used is simple correlation analysis, simple regression analysis, determination analysis and hypothesis testing. Based on the results of correlation coefficient calculation obtained value of 0.683, which can be said that the correlation between the effect of account representative of the intensification of activities has a relationship interpretations “strong”. Based on hypothesis testing can be seen that the value of t arithmetic T table that is equal to 4.852 2.048, it can be concluded that H0 is rejected and Ha accepted. Thus it can be concluded that the hypothesis “Allegedly Account Representative greatly effect on the intensification of activities of taxation” can be “accepted”. Intensification of activities to be optimal taxation in the Tax Office takes a big role of account representative for the main purpose of Taxation to maximize tax revenue can be implemented properly.